Optimasi Formula Tablet Floating Metformin Hidroklorida Menggunakan Polimer Guar Gum - Elim, Siska; Hadisoewignyo, Lannie; Sukarti, Emi (Jurnal Farmasi Sains dan Terapan, 2013)
Metformln hydrochloride Is an orally administered blguanlde derivative drug and functions as an anti hyperglycemic In patient with type 2 diabetes mellitus with bioavallablllty between 50-6096. Floating system Is the one method to enhance absorption and bioavallablllty of metformln hydrochloride. The purpose of this research was to determine the effect of guar gum concentration and concentration effervescent components and Interactions of both components on physical properties of tablets, floating lag time, floating time, and dissolution rate constant and get the optimum formula with drug release pattern according to zero order kinetics. In this research using factorial design with two factors Is concentrations factor of guar gum at 15-2096 and concentrations factor of effervescent components Is citric acid and sodium bicarbonate (1:1) at 5-1096. The method used Is direct compression method. Concentration of guar gum have a significant effect on floating lag time and dissolution rate constant but do not have a significant effect on tablet hardness. While the concentration of effervescent components not have a significant effect on tablet hardness and dissolution rate constant but a significant effect on floating lag time. Interaction between guar gum concentration and concentration effervescent components not have a significant effect on tablet hardness, floating lag time, and dissolution rate constant Based on Design - Expert program optimization, the optimum formula obtained Is formula with combination 19,596 guar gum concentration and 5,596 concentration effervescent components which resulting 11,43 Kp hardness, floating lag time 8,69 min and K dissolution 0,324 mUmln.